Nutraceutical Analysis of Marticaria recutita (Chamomile) Dried Leaves and Flower Powder and Comparison between Them - Ekta Singh Chauhan; Jaya Aishwarya (International Journal of Phytomedicine, 2018)
Chamomile is known as German Chamomile (Marticaria recutita) and Roman Chamomile (Chamaemelum nobile) a very famous daisy plant. The work mainly focuses on the nutraceuticals potential of Chamomile leaf and flower of this plant. The nutrient contains of the leaf and flower power was determined by various methods. The phytochemicals screening of the leaf and flower aqueous extract was performed by the different procedure. Leaf of this plant is rich in carbohydrate, protein, fat and also rich in vitamin C, iron, zinc and calcium. Whereas flower is rich in moisture and fiber as compared to leaf. The aqueous extract of leaf of Chamomile showed the presence of steroids, terpenoids, flavonoids, tannins and saponins and flower were lacked in alkaloids, saponins, gelatin and phenolic compounds. The results record that leaf and flowers powder contains different types of nutrients and phytochmicals in it. Chamomile is rich in different bioactive compounds, antioxidant and phytochemicals; carries many pharmacological and traditional properties. Leaves, flowers and stems of Chamomile are used as anti-oxidant, analgesic, anti-viral, anti-inflammatory, anti-septic, anti-diabetic, anti-proliferative, anti-bacterial activities and many more diseases. This paper put a light on nutrient content and phytochemical properties of Chamomile leaf and flower.